Interrogating the effect of environmental factors on e-commerce institutionalization in Tanzania: a test and validation of small and medium enterprise claims. Issue 1 (2nd January 2017) - Kabanda, Salah; Brown, Irwin
ABSTRACT: The purpose of this study is to interrogate the claims made by small and medium enterprises (SMEs) in Tanzania regarding the environmental factors that negatively affect their institutionalization of e-commerce. SMEs made claims that there was a lack of institutional readiness for e-commerce in Tanzania, as well as inadequate market forces readiness, supporting industry readiness, and socio-cultural readiness. A content analysis approach was used to interrogate institutional policy documents to determine the frequency of use of specific arguments that either support or negate the SMEs' claims. The theory of communicative action was used as a framework to analyze the truthfulness, sincerity, clarity, and legitimacy of the claims made. The findings from the content analysis show that the Tanzanian Information, Communication and Technology (ICT) policy and SME policy pay scant attention to e-commerce readiness factors. The validity claim analysis did not reveal distorted communications by SMEs, but corroborated their claims that indeed environmental factors were not conducive to the institutionalization of e-commerce in Tanzania. These findings call for a national-level reassessment of e-commerce policies in Tanzania.